Hepatotoxicity Effects of Alcohol Consumption during Paracetamol Therapy of Malaria Patients - Dinge, Fonny; Alfian, Sofa D.; Abdulah, Rizky; Sumiwi, Sri A. (Universitas Padjadjaran, Indonesia)
The risk of paracetamol induced hepatotoxicity could increase with alcohol consumption.Paracetamol was usually given to tropical malaria patients to treat fever. The aim of this studywas to determine the hepatotoxicity effect of alcohol consumption in malaria tropica patientsreceiving paracetamol. This study was a cross-sectional study which was conducted duringApril-June 2015 at a hospital in Jayapura, Indonesia. The data were obtained from questionnairesand medical records. Alcohol status was determined by Short Michigan Alcoholics ScreeningTest (SMAST) questionnaire. Level of ALT, AST and bilirubin were observed before and afterreceiving paracetamol therapy for 5 days. Based on the results, the ALT and bilirubin levels ofalcoholic group were higher than in non-alcoholic. However, chi-square test showed that alcoholstatus did not have a significant influence in ALT, AST, and bilirubin levels. Otherwise,logistic regression analysis showed that age gave a significant effect on AST level (P=0.067).Keywords: alanine aminotransferase (ALT), aspartate aminotransferase (AST), alcohol,malaria